Analisis Konflik Sosial dalam Novel Saga dari Samudra karya Ratih Kumala: Kajian Sosiologi Sastra - Sihombing, Tania Sagita; Suntoko, Suntoko; Hartanti, Dian (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2024)
Conflict is a social phenomenon that still often occurs in society, and novels can serve as an effective educational medium to introduce various types of social conflicts to students. This research aims to describe the social conflict contained in the novel Saga of the Ocean by Ratih Kumala. The method used in this research is descriptive qualitative with literary sociology approach. The data collected is in the form of descriptions of words and images, not in the form of numbers, relating to social conflicts identified through the analysis of the novel. This research analyzes social conflicts using Alwi's theory of conflict, which classifies conflicts based on the nature and position of the perpetrators. The findings of this research identify different types of conflicts that are relevant to be studied in the context of society. In addition, this research also reveals the attitudes of the characters in dealing with problems or conflicts, which can be an example for readers. From the classification results, readers can understand the causal relationship behind the conflict.